Systematic Review of Occupational Therapy Interventions to Enhance Cognitive Development in Children 0–5 Years: Part 2, At-Risk Due to Environmental Factors and Promoting Cognitive Development. Issue 4 (2nd October 2021) - Niblock, Jayna; Frolek Clark, Gloria; Crane Vos, Taylor; Lieberman, Deborah; Hunter, Elizabeth G.
ABSTRACT: Aim: This article is the second part of a systematic review updates and broadens a previous systematic review (Frolek Clark & Schlabach, 2010) to examine the evidence for of interventions within the scope of occupational therapy practice to enhance cognitive and pre-academic development in young children with or without at-risk factors. This article is Part 2 of the review and will focus on interventions for children at-risk from environmental factors and interventions that promoting cognitive development in children ages birth to 5 years. Part 1 is published separately and focuses on children with specific diagnoses. Methods: A systematic search of studies published from 2010 to 2020 using MEDLINE, PsycINFO, CINAHL, ERIC, OTseeker, and Cochrane was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Twenty-seven studies met the inclusion criteria and were critically appraised: 19 Level I, 6 Level II, and 2 Level III evidence (Part 2). Two themes are discussed within this paper (Part 2): Children At-Risk of Cognitive Delays due to Environmental Factors, and Promoting Cognitive Development. Strong strength of evidence exists for cognitive and executive functioning training programs, literacy programs, and parent interactions focused on child's needs. Strong strength of evidence indicates explicit Tier II interventions assist preschool children in learning early literacy skills (e.g., print knowledge, letter names, letter sounds). Moderate strength of evidence supports using movement or play to enhance cognitive and executive functions in preschoolers. Conclusions: Occupational therapy practitioners working in home and preschool programs can use these evidence-based interventions to enhance cognitive development, executive functions, and pre-academic functions performance for young children with or without risk factors. Part 1 of the review also appears in this issue.